Occult Hepatitis B Virus Infection among β-Thalassemia Major Patients in Ahvaz City, Iran - Amirhashchi, Fatemeh; Azaran, Azarakhsh; Seyedian, Seyed Saeid; Jalilian, Shahram; Keikhaei, Bijan (The American journal of tropical medicine and hygiene, 2021)
Occult Hepatitis B Infection (OBI) is a critical risk factor for triggering post-transfusion hepatitis (PTH), cirrhosis, hepatocellular carcinoma, and hepatitis B virus (HBV) reactivation, which β-thalassemia major (BTM) patients are at risk of it due to multiple blood transfusions. This study was aimed at determining the prevalence of OBI among BTM patients from Khuzestan Province, Iran. In this cross-sectional study, 90 thalassemia patients, who have received blood 36 to 552 times, participated referred to the Shafa hospital of Ahvaz city from January 2018 to April 2019. ELISA for determining serological markers (HBsAg, anti-HBc, anti-HBs, and anti-HCV) and real-time PCR for detecting HBV-DNA were performed; Nested PCR was conducted for DNA sequencing and determining the genotype of OBI case. Phylogenetic and statistical analyses were done by R package. Of 90 subjects enrolled in this study; 95.5% (86/90) were HBsAg negative, and the frequency of OBI among them was 1.16% (1/86). The anti-HBs, anti-HBc, and anti-HCV were detected in 80.00%, 7.78%, and 12.2% of patients, respectively. HBV-DNA was assessed at four HBsAg-positive subjects as well, and all of them were negative. The phylogenetic analysis showed that the detected HBV DNA in the OBI case belongs to the genotype D. This research, for the first time, demonstrated that OBI is present among β-thalassemia patients in Iran. Also, further studies are necessary to determine the actual prevalence of OBI among BTM patients in Iran to decisions concerning OBI screening, especially in transfusion centers.